Activation of glucagon‐like peptide‐1 receptors and skilled reach foraging. (8th August 2020) - Vestlund, Jesper; Bergquist, Filip; Licheri, Valentina; Adermark, Louise; Jerlhag, Elisabet
Abstract: Glucagon‐like peptide‐1 receptor (GLP‐1R) agonists, such as exendin‐4 (Ex4), liraglutide and dulaglutide, regulate glucose homeostasis and are thus used to treat diabetes type II. GLP‐1 also contributes towards a variety of additional physiological functions, including suppression of reward and improvement of learning. Acute activation of GLP‐1R in the nucleus accumbens (NAc) shell, an area essential for motivation, reduces the motivation to consume sucrose or alcohol when assessed in a simple motor task. However, the effects of repeated administration of the different GLP‐1R agonists on behaviours in a more complex motor task are unknown. The aim was therefore to investigate the effects of repeated Ex4, liraglutide or dulaglutide on the motivation and learning of a complex motor tasks such as skilled reach foraging in the Montoya staircase test. To explore the neurophysiological correlates of the different GLP‐1R agonists on motivation, ex vivo electrophysiological recordings were conducted. In rats with an acquired skilled reach performance, Ex4 or liraglutide but not dulaglutide reduced the motivation of skilled reach foraging. In trained rats, Ex4 infusion into NAc shell decreased this motivated behaviour, and both Ex4 and liraglutide supressed the evoked field potentials in NAc shell. In rats without prior Montoya experience, dulaglutide but not Ex4 or liraglutide enhanced the learning of skilled reach foraging. Taken together, these findings indicate that the tested GLP‐1R agonists have different behavioural outcomes depending on the context. Abstract : The glucagon‐like peptide‐1 receptor (GLP‐1R) agonists, exendin‐4 (Ex4) and liraglutide (Lir) reduces the motivation to skilled reach foraging in rats that have acquired this behaviour, whereas dulaglutide (Dul), enhances the learning of this behaviour in rats without prior experience.